1994
DOI: 10.1002/mc.2940090304
|View full text |Cite
|
Sign up to set email alerts
|

Dna polymerase arrest by adducted trivalent chromium

Abstract: Carcinogenic chromium (Cr6+) enters cells via the sulfate transport system and undergoes intracellular reduction to trivalent chromium, which strongly adducts to DNA. In this study, the effect of adducted trivalent chromium on in vitro DNA synthesis was analyzed with a polymerase-arrest assay in which prematurely terminated replication products were separated on a DNA sequencing gel. A synthetic DNA replication template was treated with increasing concentrations of chromium(III) chloride. The two lowest chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
0
4

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 59 publications
10
77
0
4
Order By: Relevance
“…Our observations are consistent with other spectroscopic studies that showed no major Cr(VI)-DNA interaction in vitro in the absence of reducing agents (5,8,30). However, in the presence of metabolizing system, where Cr(VI) is reduced to Cr(III), major Cr(III)-DNA complexation has been observed (5,8,10,11).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our observations are consistent with other spectroscopic studies that showed no major Cr(VI)-DNA interaction in vitro in the absence of reducing agents (5,8,30). However, in the presence of metabolizing system, where Cr(VI) is reduced to Cr(III), major Cr(III)-DNA complexation has been observed (5,8,10,11).…”
Section: Resultssupporting
confidence: 92%
“…When the concentration of Cr(III) increased further, DNA-DNA cross-links occurred to inhibit the polymerase activity. Trivalent chromium can bind purified DNA and form lesions capable of obstructing DNA replication in vitro (10,11). It has also been observed that intact Novikoff ascites hepatoma cells exposed to potassium chromate formed cross-linking of nuclear proteins to DNA (12).…”
mentioning
confidence: 99%
“…Treatment of pSV2neoTS with CrCl3 resulted in the dose-dependent formation of truncated molecules (Figure 7). After treatment with relatively low concentrations of CrCl3 (35, (36). A similar inhibition of polymerase action via the formation of chromium (III)-induced DNA-DNA cross-links has previously been reported by Snow and Xu (45).…”
Section: Discussionsupporting
confidence: 70%
“…Because no chromium deficiency has been consistently reported amongst healthy human populations (Stallings and Vincent 2006;Stearns 2007), the fact of its ''essentiality'' remains a controversial matter (Stearns 2000;Levina et al 2003;Stallings and Vincent 2006). Furthermore, because chromium may accumulate and is possibly genotoxic to animals and humans (Smith 1970;Debetto and Luciani 1988;Snow 1991;Bridgewater et al 1994;Stearns et al 1995;Błasiak and Kowalik 2000), excessive chromium intake (or exposure) should be avoided. For the two categories of adults in our study, the median and 95th percentile values are, respectively, 0.6 and 1.9 % (consumers of WB meat only) and 1.1 and 3.5 % (consumers of WB meat plus liver) of the safe limit established by the WHO (1996).…”
Section: Cadmium Lead and Chromium Exposure Assessments For Huntersmentioning
confidence: 99%